2012
DOI: 10.1158/1535-7163.mct-12-0162
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dendritic Cell Maturation by the Tumor Microenvironment Correlates with the Survival of Colorectal Cancer Patients following Bevacizumab Treatment

Abstract: Development of bevacizumab has improved survival in colorectal cancer, however, currently there are no biomarkers that predict response to bevacizumab and it is unknown how it influences the immune system in colorectal cancer patients. Dendritic cells are important for the induction of an antitumor immune response; however tumors are capable of disabling dendritic cells and escaping immune surveillance. The aim of this study was to assess the numbers of CD11cþ cells infiltrating tumor tissue and to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
1
35
0
1
Order By: Relevance
“…Nevertheless, our data show that the proper function of a comprehensive network of immune response genes is of vital importance for the survival of colorectal cancer patients. Recent results indicating that the tumor microenvironment can reduce the maturation of dendritic cells [49,50] hint to the importance of our findings and suggest avenues for prognosis and treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, our data show that the proper function of a comprehensive network of immune response genes is of vital importance for the survival of colorectal cancer patients. Recent results indicating that the tumor microenvironment can reduce the maturation of dendritic cells [49,50] hint to the importance of our findings and suggest avenues for prognosis and treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, esophageal epithelial cells expressing HLA-DR have been shown to have functional ability and can effectively process and present antigens to T cells [12]. Therefore, it is possible that HLA-DR upregulation by tumor epithelial cells plays a direct functional role in anti-tumor immunity, potentially acting as a compensatory mechanism for tumor-induced inhibition of professional antigen-presenting cells such as dendritic cells, as previously shown by our group in colorectal cancer [32]. …”
Section: Discussionmentioning
confidence: 81%
“…We have previously demonstrated that the TME of advanced colorectal cancer (CRC) suppresses monocyte-derived dendritic cell (MDDC) maturation and IL-12p70 secretion (Michielsen et al , 2011). Importantly, the degree of this inhibition correlated with the survival of stage IV patients receiving bevacizumab therapy (Michielsen et al , 2012). Although changes in DC phenotype have been noted in both colorectal (Gulubova et al , 2012) and ovarian (Scarlett et al , 2012) cancer progression, it is not clear if the immunosuppressive nature of the TME varies with disease progression in colorectal cancer.…”
mentioning
confidence: 99%
“…Here we used our established tumour explant model (Michielsen et al , 2011, 2012) to determine if the microenvironment of earlier staged tumours is as suppressive as that of patients with metastatic disease. In addition we characterised the phenotype of non-metastatic CRC patients' MDDCs and examined production of IL-12p70 in response to lipopolysaccharide (LPS) in both the absence and presence of tumour-conditioned media.…”
mentioning
confidence: 99%